Short timescale variability in large-amplitude internal waves on the western Portuguese shelf. (1st September 2022) - Magalhaes, Jorge M.; da Silva, Jose C.B.; Nolasco, Rita; Dubert, Jesús; Oliveira, Paulo B.
Abstract: Timescales in the ocean can range from the transient turbulence to the long-term climate scales. Quantifying its changes involves establishing meaningful background states, but that can be challenging if an extensive array of wave phenomena is masking the ocean's variability. Internal Waves (IWs) are a fundamental part of these wave phenomena, which are now widely acknowledged as major contributors in ocean dynamics. In this study we use satellite imagery from Synthetic Aperture Radars (SAR) and moored temperature records to assess the variability scales and magnitudes of coastal IW systems propagating onshore off the western Portuguese shelf. The data shows significant variability in timescales of just a few days, and hence within the waves' typical propagation lifespan. A regional ocean circulation model is used together with linear theory to assess how mesoscale variability is contributing to the observed variability patterns observed in the IWs in the SAR and in situ data. According to linear theory, the IW variability is mostly owing to variable mesoscale currents, which off the Portuguese coast typically result from geostrophic flows, eddies and upwelling dynamics. IW variability owing to changes in stratification is found to amount to about half of that in background flows, but their effect can go unnoticed within the largest contributions from mesoscale currents. One extreme event is highlighted in which IWs from consecutive tidal cycles could possibly decouple from (i.e. not traceable back to) their originating tides in just a few days and hence within their typical lifespans. Highlights: In situ and SAR evidence show Short timescale variability in large-amplitude internal waves on the western Portuguese shelf. Data shows significant variability in timescales of a few days, and hence within the waves' typical propagation lifespan. IW variability is mostly owing to variable currents. Variability from stratification is half of that in background flows. An extreme event is shown in which consecutive IWs can decouple from their originating tides in a few days.